When the carbon being dated is not what you think it is: Insights from phytolith carbon research. (1st October 2018) - Santos, Guaciara M.; Masion, Armand; Alexandre, Anne
Abstract: For proper interpretation of radiocarbon ( 14 C) age results, the carbon fraction being dated must be identified beforehand, ideally as a single homogeneous entity that best represents the event being studied. Radiocarbon dating of fossil phytoliths (biosilica formed in living higher-plants) has been used in a number of archaeology and paleoenvironmental studies. More precisely, the carbon occlusion (phytC) has been 14 C dated. This method relies on the phytC being photosynthetic in origin, so that its 14 C signature is similar to that of the host plant. However, we have recently presented overwhelming evidence that phytC in modern plants is made up of a mixture of carbon photosynthesized by the plant (from atmospheric CO2 ) and soil carbon comprised of multiple 14 C signatures (ages). The discussion presented here is based on our assessments of phytC 14 C signatures, their chemical nature, location, origin and fate as well as the current state of knowledge on plant cell silica interactions with biomolecules. Finally, regardless of the fact that there are cases where fossil phytC 14 C results appear to match expected values, the impossibility of establishing a priori either the amount of the soil carbon contribution to phytC or the mean 14 C age of its occluded mixed pool precludes the use of phytoliths as a reliable 14 C dating tool.